Selective Reduction of Carbon Dioxide in Water Using [M(bpy2+)(CO)3(I)]2+ (M = Mn, Re) Electrocatalysts with Pendent Cations - Preshit C. Abhyankar; Dmitry E. Polyansky; Gerald F. Manbeck (Journal of the American Chemical Society, 2026)
Abstract Manganese(I) carbonyl complexes are promising electrocatalysts for CO2 reduction, yet their application in homogeneous aqueous media remains limited by poor solubility and selectivity. Here, we report water-soluble Mn(I) and Re(I) complexes fac-[M(bpy2+)(CO)3X]2+ (X = I or Cl), featuring bipyridine ligands functionalized with −Ph−CH2–(NMe3)+ cationic ammonium groups that integrate water solubility with secondary-sphere stabilization. In a bicarbonate buffer at pH 6.8, the Mn catalyst is completely selective for CO production at a low overpotential (η = 0.3 V), operating by a protonation-first mechanism with observed rates of ∼10 s–1. Pulse radiolysis reveals that the one-electron-reduced Mn species undergoes dimerization in the absence of CO2 but reacts competitively with CO2 through an initial pre-equilibrium followed by fast formation of a dinuclear CO2-bridged species (ΔGo = −12.4 kcal mol–1). At a higher 0.6 V overpotential, a faster reduction-first pathway (∼100 s–1) is available upon reduction of the metallocarboxylic acid intermediate, Mn-CO2H2+; however, this regime is functionally limited by the formation of a resistive, noncatalytic film on the electrode surface. Comparison to the analogous water-soluble Re catalyst (kobs = 440 s–1, η = 0.6 V) highlights the distinct mechanistic advantages of earth-abundant Mn in low-potential catalysis. These results demonstrate how cationic second-sphere design enables selective, homogeneous CO2 reduction in water while revealing competing radical and electrode-mediated processes that govern catalytic performance.